Detection of Uterine Leiomyosarcoma Peritoneal Lesions by SPECT/CT and ROLL Technique. (October 2019) - Manca, Gianpiero; Garau, Ludovico Maria; Romanini, Antonella; Rubello, Domenico; Nuzzo, Amedeo; Barbarello, Linda; Fantechi, Lorenzo; Colletti, Patrick M.; Boggi, Ugo; Volterrani, Duccio
Abstract : Abstract: We reported the preoperative radio-guided localization of 4 peritoneal metastatic nodules in the case of a 45-year-old woman with uterine leiomyosarcoma. Three lines of chemotherapy were tried, but cardiotoxicity occurred. Within the context of so-called GOSTT (guided intraoperative scintigraphic tumor targeting), preoperative radio-guided localization of peritoneal metastases enabled their subsequent radio-guided excisional biopsy. SPECT/CT allowed for anatomical localization of the hot lesions and generated a 3-dimensional volume-rendering roadmap, facilitating a surgical approach.